Conceptual Study of Ethical, Legal and Professional Considerations in Counseling Assessment - Jumli Sabrial Harahap; Erlindawati Erlindawati; Wahidah Fitriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Aim: This research aims to find out and reveal ethical, legal and professional considerations in assessments. Method: The method used in writing this article is a literature review. Data collection techniques by analyzing the results of previous research journals. Data analysis uses qualitative descriptive techniques. Result and Disscusions: The results of this research reveal that ethical, legal and professional considerations in counseling assessments are very important. Conclusion: Counselors must maintain client confidentiality, provide clear information, and obtain written consent. Counselors are required to comply with laws regarding data privacy and client rights, and use valid and reliable assessment tools with appropriate competence. Ensure safe, fair and beneficial services for clients.